Analysis of Technical Efficiency of Groundnut Production in Wukari Local Government Area of Taraba State, Nigeria - A, Olayiwola S.; A, Oniga M. (Darul Yasin Al Sys, 2024)
The study analyzed the technical efficiency of groundnut production in Wukari Local Government of Taraba State, Nigeria. A multistage sampling technique was employed in the study with the use of 120 structured questionnaires. The result showed that majority of the farmers were male with mean age of 39.18 years. Majority (53.35%) were married, the average mean of the household size was 7.14 and farm size was 3.61, which was acquired through inheritance (42.5%). Also, 30.8% of the respondents used family labor and 57.5% of the respondents having <100000 as their income level. Average gross margin for groundnut production in the study area was N147,513.92/ha. The return on investment was estimated to be N0.55, which implies that for every N1 expended, the farmer is expected to earn N0.55 in return. The result from the technical efficiency showed that farm size, fertilizer, seed and labour were all significant while the result from the technical inefficiency showed that educational level, farming experience, age and farm size were all significant. In conclusion, the study shows that groundnut production is a profitable business and was recommended that groundnut producers be encouraged to increase their scale of production to increase their yield, stakeholders in the sector should make provision for incentives such as in-service extension training to improve groundnut productivity also, implementation of policies that would encourage farm owners to form cooperative/organization or join the existing ones in the study area.